Questions   
Sort: 
 #1
avatar+502 
0
Rauhan Dec 30, 2017
 #1
avatar+5929 
+1

Question 1

 

a)     f( x )  =  3x2 - 5x + 6    and    g(x)  =  x2 + 3x

 

f o g   =   f( g(x) )

 

f o g   =   f( x2 + 3x )

 

f o g   =    3( x2 + 3x )2 - 5( x2 + 3x ) + 6    I'll let you simplify these if necessary...

 

The domain is (-∞, ∞), and from this graph, we can see that the range is  [47/12, ∞) .

 

g o f   =   g( f(x) )

 

g o f   =  g( 3x2 - 5x + 6 )

 

g o f   =   ( 3x2 - 5x + 6 )2 + 3( 3x2 - 5x + 6 )

 

The domain is  (-∞, ∞), and from this graph, we can see that the range is  [3901/144, ∞) .

 

 

b)     f(x)  =  2x    and    g(x)  =  3 - x

 

f o g   =   f( g(x) )

 

f o g   =   f( 3 - x )

 

f o g   =   23 - x

 

The domain is  (-∞, ∞), and the range is  (0, ∞) .

 

g o f   =   g( f(x) )

 

g o f   =   g( 2x )

 

g o f   =   3 - 2x

 

The domain is  (-∞, ∞), and the range is  (-∞, 3) .

 

 

c)     f(x)  =  sin x    and    g(x)  =  x

 

f o g   =   f( g(x) )

 

f o g   =   f(  x  )             We already know that  f(x)  =  sin x , so....

 

f o g   =   sin x

 

The domain of this is  (-∞, ∞), and the range is  [-1, 1] .

 

g o f   =   g( f(x) )

 

g o f   =   g( sin x )     Plug in  " sin x "  for  " x "  into the function  g(x) .

 

g o f   =   sin x

 

The domain is  (-∞, ∞),  and the range is  [-1, 1] .

hectictar Dec 30, 2017

6 Online Users

avatar
 
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details